Classification Of Factors Influencing Diabetes Mellitus Type II By Using Multivariate Adaptive Regression Spline At Rantau Prapat Regional Hospital - widya panjaitan; Hendra Cipta (Department of Mathematics, Hasanuddin University, 2024)
Diabetes Mellitus is a metabolic disease caused by increased levels of glucose or blood sugar. Diabetes Mellitus is divided into three different types: type I diabetes, type II diabetes, and gestational diabetes or diabetes during pregnancy. Type 2 diabetes mellitus affects 90–95% of diabetics. The aim of this research is to identify related factors that influence Type II Diabetes Mellitus by applying the Multivariate Adaptive Regression Spline (MARS) Method. The model with the lowest Generalized Cross-Validation (GCV) score among the models constructed is considered the best model. The research findings show that BF=10, MI=3, and MO=0 are the optimal parameter combinations for the MARS model with a GCV value of 0,09582998 . According to research using MARS, the predictor variables with an 89.33% classification accuracy that affect the blood glucose levels of Type II Diabetes Mellitus patients include Age (X1), Gender (X2), Blood Pressure (X3), and Comorbidities (X5).